Reflection of Pawongan Values in the Characterization of The Big Friendly Giant - Ni Kadek Githa Valentina; Ni Komang Arie Suwastini; Ni Wayan Surya Mahayanti; Ni Nyoman Artini; I Gusti Ngurah Agung Wijaya Mahardika (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2025)
Global children’s literature is often examined from the perspectives of aesthetics and universal moral messages without being contextually linked to the local cultural values of readers. Consequently, the potential of children’s literature as a medium for character education based on local wisdom has not been fully utilized. This study aims to analyze, evaluate, and interpret the reflection of Pawongan values, as part of the Tri Hita Karana philosophy, in the characterization of the Big Friendly Giant (BFG) in Roald Dahl’s novel The BFG. The research employs a qualitative approach with a descriptive-interpretative design. The subject of the study is a single fictional character, the BFG, with units of analysis consisting of the character’s actions, dialogues, and interpersonal interactions across various narrative sequences and sub-sequences. Data were collected through documentation studies involving intensive and repeated readings of the novel text using research instruments. Data analysis was conducted using the interactive qualitative analysis model by Miles, Huberman, and Saldaña, which includes data collection, data condensation, data display, and conclusion drawing and verification. The findings indicate that the BFG consistently reflects five core Pawongan values: responsibility, communicative behavior, tolerance, respect, and perseverance, with responsibility and communication being the most dominant values. Overall, the study concludes that global children’s literature can serve as an effective medium for character education when interpreted through the lens of local wisdom. The study’s implications emphasize the importance of integrating local cultural values into literary studies and EFL instruction to strengthen contextual and meaningful character education.